Current Trends in Project Management: Mixed Research of ‘Gymnastic’ Enterprise Concept - S. A. Titov; N. V. Titova (Управленческое консультирование)
Project management plays significant role in modern economy and public administration. Project management trends have a great impact on the performance of projects and enterprises, methods and tools of management, training programs for managers. The ≪Pulse of the Profession ≫ survey, regularly published by the Project Management Institute, allows tracking current trends in project management practice. In 2021, the ≪Pulse of the Profession≫ was dedicated to a new concept — the ≪gymnastic≫ enterprise. In this article, the authors analyze the text of ≪Pulse of the Profession≫, 2021 using mixed research methods including qualitative and quantitative content analysis tools. The results show the closeness of the ≪gymnastic≫ enterprise concept to the concept of organizational ambidexterity. A content analysis helped to identify the key organizational practices of ≪gymnastic≫ enterprise, such as the situational use of hybrid project management methodologies and methodological pluralism, the combination of structural coherence and flexibility in project management processes, the active use of entrepreneurial and innovative methods and approaches, as well as tools and techniques for talent management, organizational change and learning. The indicated practices allow ≪gymnastic≫ enterprises to achieve better results in comparison with ≪traditional≫ companies. The results also indicate the ability of the ≪gymnastic≫ enterprise concept to influence project management practice, educational and training programs and consulting services in the field of project management.